The Application of Spiritual Emotional Freedom Technique on Pain in Cancer Patients - Sukesi Niken; Wahyuningsih Wahyuningsih; Heny Prasetyorini (Indonesian Journal of Global Health Research, 2020)
Cancer patients often experience pain complaints on their parts of body. The pain felt by patients can interfere with the patient's daily activities, leading to a decreased quality of life. The provision of Spiritual Emotional Freedom Technique (SEFT) to cancer patients is done to help overcome the problem of physical and psychic pain. This therapy combines body energy and spiritual therapy using three stages consisting of the setup, the tune in, and the tapping. A mild tapping or tapping method is given at 18 points on the body. This study aimed to find out the extent of the effect of SEFT on the pain of cancer patients. This research was a descriptive through a case study approach. The number of participants was 4 participants. The sampling was done purposively. The inclusion criteria of this study are cancer patients who complained moderate to severe pain. The pain level was measured using the Numeric Rating Scale (NRS). The data were collected using literature studies, in-depth interviews, and observations. Data analysis was done by using an interactive model that classifies the process into data reduction, data presentation, and conclusion drawing (Verification). The application of case studies using SEFT theory has a meaningful influence to reduce pain.